Legal problems concerning pre-contractual liability - KITTICHOCKWATTANA, KOTCHAMOL (Law for Development Graduate Journal, 2025)
This article aims to study pre-contractual liability principles in Thailand, France, and Italy, and to conduct analytical and comparative research on the definitions, clarity of pre-contractual liability principles, and legal interpretations. The study compares foreign implementation approaches with Thailand’s approach to improve the effective application of pre-contractual liability principles. The research finds that Italy and France currently implement pre-contractual liability principles with relatively similar approaches. Furthermore, Italy has incorporated pre-contractual liability provisions into its Civil and Commercial Code, resulting in clear and consistent interpretations, as well as fair protection and remedies for parties acting in good faith. In contrast, Thailand still lacks clarity regarding the definition and current implementation of pre-contractual liability principles. Some scholars agree with these principles while others disagree, and the legal codes do not contain specific provisions on this matter. When pre-contractual liability issues arise, existing legal principles must be applied, which often prove inadequate due to mismatched liability elements. This may result in unfairness to good-faith parties due to the absence of statutory provisions or definitions that could provide appropriate remedies for injured parties. Therefore, it is advisable to revise the definition and implementation of pre-contractual liability principles in Thailand, following the examples of Italy and France. Moreover, consideration should be given to codifying these principles in the legal code, as Italy has done, to support this doctrine. This would enhance the protection of parties’ rights, promote fairness, and establish more uniform standards.